(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The research aims to identify the effect of interactive agility exercises in developing the speed of foot movements, some physical and visual abilities, and the level of skill performance among the epee players under study. The research sample was (12) epee fencing players under 15 years of age, and they were divided into an experimental group and their number (4) players to whom the proposed training program under study (interactive agility training) was applied. The other was a control group, numbering (4) players, to whom the traditional program was applied (by the coach), in addition to the exploratory research sample from within the original community, numbering (4) players, who were chosen. In the intentional method of Maadi Sports Club players for the 2020/2021 sports season, the researcher used the experimental method for two groups, one experimental and the other a control group, using the pre-post score. The researcher found that there were statistically significant differences between the level of performance of some physical, visual and skill abilities and the speed of foot movements, as the impact of the proposed training program Using interactive agility exercises, the level of the physical variables under study (transitional speed - agility - accuracy - flexibility - balance - coordination) and the speed of foot movements (advance time for 14 m, retreat time for 14 m, lunge for 30 seconds, advance and retreat with the diastolic movement for 30 seconds) are developed. , regression and advancement with the diastolic movement for 30 seconds), and some visual abilities (coordination between the eye and the armed arm, coordination between the eyes and the legs, coordination between the eye and the armed arm and the legs), and the level of skill performance (straight attack, raiding attack, cutting attack) of the group’s epee players. The experimental study is under study, and the impact of the training program developed by the coach on the level of physical, visual and skill variables and the speed of foot movements is under research for the epee players of the control group under research. The researcher attributes this difference to the application of the proposed training program using interactive agility training. The researcher recommends paying attention to interactive agility training. In training programs to develop the level of physical, visual and skill abilities and the speed of foot movements of fencing players, and the use of modern methods in training on the speed of foot movements of male and female fencing players.